Optimalisasi Paket Wisata Pada Pantai Sawarna Menggunakan Aplikasi Sitaman Bumi Yang Terintegrasi Dengan Batour - Ramdhani Mahbub, Asep; Ardiansyah, Jerry; Syahroni, dkk, Muhammad (VIDHEAS: Jurnal Nasional Abdimas Multidisiplin, 2023)
Sawarna Village in Lebak, Banten, possesses significant tourism potential yet remains underutilized and has experienced a decline in visitors due to the COVID-19 pandemic. Community Service Program (CSP) Group 7 focuses on managing and marketing tourism packages through digital platforms to enhance local economy and knowledge. Previously, tourism information was primarily disseminated orally, hindering Sawarna's tourism potential to reach its maximum. CSP is seen as a strategic opportunity to advance tourism potential through technology. Besides marketing, CSP empowers the community and local figures to actively participate in sustainable tourism development. The main objective is to enhance the community's capacity in managing tourism potential sustainably. The method employed involves comprehensive data collection of tourism packages and optimization of existing tourist attractions. The outcome is the creation of structured and digitally interconnected tourism packages, facilitating access to information for tourists and boosting Sawarna's competitiveness as a tourism destination. CSP is expected to serve as a catalyst in unlocking new opportunities for Sawarna as a competitive tourism destination. In conclusion, the management and marketing of tourism packages through digital platforms are crucial in maximizing Sawarna's tourism potential and increasing community involvement in sustainable tourism development